PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, TRANSAKSIONAL, KEPUASAN KERJA TERHADAP OCB KARYAWAN PT.KONSTRINDO PUTERA PERKASA - ARIANSYAH INDRA, BATARA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2016)
This study aims to find out Transformational Leadership Style, Transactional Leadership Style and Job Satisfaction have influence, either simultaneously or partially, to Organizational Citizenship Behavior (OCB) Employee PT.Konstrindo Putera Perkasa. The sample in this study using all the population with the method used is saturated or census sampling. Data collection was done by using questionnaires, interviews, and through observation (observation). This study uses Multiple Linear Regression Analysis Method with the help of computer program SPSS For Windows Release 17.0.The result of hypothesis analysis and testing can be concluded that: (1) based on results obtained by Sig.F0.000 <0,05, which can be interpreted that the variables of transformational leadership style, transactional leadership style and job satisfaction simultaneously affect the Organizational Citizenship Behavior (OCB) variable. (2) based on the regression test results, the variables of transformational leadership style have significance level t sig. (0,000) <? (0,05), transactional leadership style variable has significance level t sig. (0.019) <? (0,05) and job satisfaction variable have significance level t sig. (0,05) <? (0,05), so that variable of transformational leadership style, transactional leadership style and satisfaction of work partially influence to organizational citizenship Behavior (OCB) variable (3) based on result of regression test obtained variable which influenced most dominant is transformational leadership style has the highest Beta value is 0.708